A Randomized Phase 2 Study Comparing the Combination of Ficlatuzumab and Gefitinib with Gefitinib Alone in Asian Patients with Advanced Stage Pulmonary Adenocarcinoma. Issue 10 (October 2016) - Mok, Tony Shu Kam; Geater, Sarayut Lucien; Su, Wu‐Chou; Tan, Eng‐Huat; Yang, James Chi‐Hsin; Chang, Gee‐Chen; Han, May; Komarnitsky, Philip; Payumo, Francis; Garrus, Jennifer E.; Close, Sandra; Park, Keunchil
ABSTRACT : Introduction: : A randomized phase 2 study was designed to compare the combination of ficlatuzumab (AV‐299), a humanized hepatocyte growth factor–neutralizing monoclonal antibody, plus gefitinib versus gefitinib monotherapy in a pulmonary adenocarcinoma population clinically enriched for EFGR tyrosine kinase inhibitor–sensitizing mutations. Methods: : A total of 188 patients were randomized 1:1 to receive either gefitinib or ficlatuzumab plus gefitinib treatment. Patients who demonstrated disease control in the single‐agent gefitinib arm were allowed to cross over to ficlatuzumab plus gefitinib treatment upon disease progression. Molecular analyses included tumor EGFR mutation status and retrospective proteomic testing using VeriStrat, a multivariate test based on mass spectrometry. Results: : The addition of ficlatuzumab to gefitinib did not provide significant improvement over gefitinib monotherapy for the primary end point of overall response rate or the secondary end points of progression‐free survival and overall survival. In the subgroup classified as VeriStrat poor, the addition of ficlatuzumab to gefitinib showed significant improvement in both progression‐free survival and overall survival in both the intent‐to‐treat population and the subgroup with EGFR tyrosine kinase inhibitor–sensitizing mutations. For all patients, the most frequent adverse events were diarrhea, dermatitis acneiform, and paronychia. Conclusions: : Although the trial showed no significant benefit from the addition of ficlatuzumab to gefitinib in the overall population of Asian patients with advanced‐stage pulmonary adenocarcinoma, the biomarker data suggest that patients classified as VeriStrat poor may benefit from ficlatuzumab combination therapy.